2151. Biofilm and Metallo-β-Lactamase (MBL) Production Among Imipenem-Resistant Pseudomonas aeruginosa and Acinetobacter spp. - Metok, Yang (Open Forum Infect Dis, 2019)
BACKGROUND: Pseudomonas aeruginosa and Acinetobacter spp. head the list of hospital-acquired infections. Resistance to carbapenem as reserve drug is under threat with the emergence of Metallo-β-lactamase (MBL) and biofilm producing bacterial strains. This study was thus undertaken to determine the rate of MBL and biofilm production among imipenem-resistant P. aeruginosa (IRPA) and imipenem-resistant Acinetobacter spp. (IRAS) isolates. METHODS: A total of 79 P. aeruginosa and 117 Acinetobacter spp. were isolated from different clinical specimens of patients visiting Manipal Teaching Hospital, Pokhara Nepal from July 2016 to January 2017. Isolation, identification and antibiotic susceptibility testing of the isolates were performed by standard microbiological techniques. Combined disc test and Epsilometer test (E-test) were employed to detect MBL in IRPA and IRAS isolates. Microtiter plate using crystal violet method was employed for detection of biofilm in imipenem-resistant isolates. RESULTS: 9 (11.4%) of P. aeruginosa and 49 (41.9%) of Acinetobacter spp. were Multidrug Resistant (MDR). Similarly, 22 (27.8%) of P. aeruginosa and 23 (19.7%) of Acinetobacter spp. were Extensively Drug Resistant (XDR). Imipenem resistance was detected among 15 (19%) P. aeruginosa and 57 (48.7%) Acinetobacter spp. isolates. 8 (53.3%) of IRPA and 22 (38.6%) of IRAS isolates were MBL producers while all (100%) of IRPA and 47 (82.5%) of IRAS were biofilm producers. All the biofilm producer IRPA isolates were XDR and 62.5% of XDR IRAS strains were moderate biofilm producers. However, 80% of IRPA, 49.1% of IRAS and 63% of both MBL producer isolates were weak biofilm formers. Polymyxin B and ampicillin-sulbactam showed a better degree of susceptibility against MBL cum biofilm producer IRPA and IRAS isolates respectively. CONCLUSION: The study showed high propensity of IRPA and IRAS to form biofilm, which is strongly associated with higher drug resistance. Such high rate of MBL and biofilm producing P. aeruginosa and Acinetobacter spp. alarms the rapid spread of such strains in our hospital setting. [Image: see text] [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.